Examining the Use of Botanicals for Managing Cnaphalocrocis Medinalis (Guenee) in Rice Cultivation in Dhadgaon, Nandurbar, Maharashtra. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Rice (Oryza sativa L.) is an important crop of our country, and its yield loss may be caused by insect pests (Kumar et al., 2015). The rice leaf folder pest is of major concern among rice pests (Kushwaha, 2004). An attempt was made to evaluate the efficacy of botanical extracts in the control of rice leaf folder infestation during the Kharif season at Dhadgaon, Nandurbar District, Maharashtra. The experiment was laid out in RBD with 5 treatments and 3 replications: Neem Seed Kernel Extract (NSKE) 5%, garlic extract 5%, Chilli extract 5%, a chemical check, and an untreated control. Botanicals were applied at 30 days, 45 days, and 60 days after transplanting (DAT). All treatments were found significantly superior in respect of the reduction of leaf damage and larval population as compared to the control. Botanical Neem seed kernel extract was found to be the most effective, with minimum leaf damage (11.2%) and a larval population (1.30), followed by garlic and chilli extracts. The maximum efficacy was observed in the chemical check. The findings revealed that Neem seed kernel extract was found to be most effective in reducing leaf damage and larval population. It can be recommended for incorporation in IPM in rice for the control of leaf folder.